Answer:..$.$!:
Step-by-step explanation:
If you move the negative on the left side of the second equation over to the right side, then we can see that the equation is equivalent to
![y={-2x} - 13](https://tex.z-dn.net/?f=y%3D%7B-2x%7D%20-%2013)
.
Remember that an equation
![y = mx + b](https://tex.z-dn.net/?f=y%20%3D%20mx%20%2B%20b)
represents a line with slope
![m](https://tex.z-dn.net/?f=m)
and y-intercept
![b](https://tex.z-dn.net/?f=b)
. Since both equations given have a slope of -2, but have different y-intercepts, they are
parallel.
Answer:
Area of circle = 465.82 cm²
Step-by-step explanation:
Given the following data;
Circumference of the hub cap = 76.49 cm
Pie, π = 3.14
To find the area of the hub cap;
First of all, we would determine the radius of the hub cap.
Mathematically, circumfeence of a circle is equal to;
C = 2πr
Where:
C is the circumference of a circle.
r is the radius of a circle.
C = 2πr
76.49 = 2 * 3.14 * r
76.49 = 6.28r
Radius, r = 76.49/6.28
Radius, r = 12.18 cm
Next, we find the area of the hub cap;
Area of circle = πr²
Area of circle = 3.14 * 12.18²
Area of circle = 3.14 * 148.35
Area of circle = 465.82 cm²
However, if the circumference of the hub cap were smaller, the area of the hub cap would also be smaller. Thus, the circumference of a hub cap is directly proportional to the area of a hub cap.
Answer:
D. 60=(x+45)
Step-by-step explanation:
They are the same degree so they should equal eachother
Answer:
у = x² + 7x - 30
Step-by-step explanation:
x₁ = 3 and x₂ = -10
Use the formula (x - x₁)(x - x₂) = 0
(x - 3)(x - (-10)) = 0
(x - 3)(x + 10) = 0
x² + 10x - 3x - 30 = 0
x² + 7x - 30 = 0